Productivity and profitability of aromatic rice production in the Philippines - Beltran, Jesusa C.; Daplin, Kristine Marie A.; Relado-Sevilla, Rhemilyn Z.; Bordey, Flordeliza H.; Manalili, Rowena G.; Arida, Imelda A.; Ante, Ralph Homer L.; Romero, Marissa V.; Leon, Teresa Joi P De; Chua, James D.; Baltazar, Marco Antonio M.; Valencia, Maria Shiela D.; et al. (Conscientia Beam, 2021)
With the 2019 implementation of the Rice Tariffication Law (RTL), prices of ordinary white rice are expected to go down as a response to the influx of cheaper rice imports. This could put the local farmers at a disadvantage and could provoke them to reduce rice cultivation. Production of aromatic rice, a type of specialty rice with pandan-like scent induced by 2-acetyl-1-pyrroline (2AP) compound, could serve as a viable enterprise for the local farmers. Covering the provinces of Oriental Mindoro and Apayao, this study was conducted to produce baseline information and gain a comprehensive understanding of the production and potentials of aromatic rice. A survey was carried out to obtain 2017 cropping season farm-level data from 82 market-oriented farmer-respondents. Descriptive statistics and costs and returns structure were employed for data analysis. Results showed that venturing into aromatic rice cultivation can be a viable enterprise for the farmers as a coping mechanism with the ill effects of RTL. Yield level of modern aromatic rice varieties is at par with the national average. Aromatic rice cultivation also appeared to be profitable. Findings showed that the current local aromatic rice industry has high potential for expansion and opportunity for import substitution. Furthermore, top aromatic rice varieties in the country must be looked into to increase profitability. With these conclusions, strategies for yield enhancement, cost reduction, and premium quality preservation are recommended.